Analisis Konstruksi Bangunan Bertingkat Terhadap Beban Gempa SNI-03-1726-2019 Dengan Infilled Frame - Maya Saridewi Pascanawaty; Agustini Ernawati; Titik Wahyuningsih (Media Ilmiah Teknik Sipil, 2021)
Red brick is one of the materials that is still quite widely used in construction practice, because it is quite easy to get and the price is relatively cheap. Red masonry wall is a pair consisting of a binder (mortar) and a filler (red brick) known as masonry. Masonry generally provides durable construction, where the constituent material, mortar quality, and workmanship greatly affect the durability of the overall wall construction. The installation of infill walls causes the structure to become more rigid, which can sometimes cause different failure behavior between structures without infill walls and structures with infill walls. This also affects the capacity and ductility of the overall structure. Several research results show that the interaction of the infill wall with the framework is very effective in increasing the strength, stiffness, and performance of the structure in resisting lateral loads due to earthquakes. This study takes the example of a 4 (four) floor building. The analysis is carried out by modeling the walls in the SAP2000 software application, where the structural models include: Model I fully uses frame elements, Model II is a structure modeled by including infill walls without plastering as a shell element, Model III is a structure modeled using infill walls with stucco reinforcement as the shell element, and Model IV is a structure modeled using infill walls with stucco reinforcement and counter wire as the shell element. The comparison parameters in this study are structural strength and deformation. Based on the results of the analysis, Model II, 90% stiffer than the open frame structure (open frame) Model I; while Model III is 92% stiffer than Model I; and Model IV, 97% stiffer than Model I which, when viewed from the X-direction earthquake load. When viewed from the Y-direction earthquake load, the infilled frame structure for Model II is 88% stiffer than the open frame structure (open frame) Model I; while Model III is 91% stiffer than Model I; and Model IV, 99 % stiffer than Model I. Moment and latitude values ​​of Model II, Model III, Model IV are smaller than Model I both in terms of the X-direction earthquake load and the Y-direction earthquake load. Infill walls of Model II are larger than those of Model IV and Model III when viewed from the X-direction earthquake load or due to the Y-direction earthquake load. and very qualified for use in areas with high earthquake risk